Dejerine–Sottas disease in childhood—Genetic and sonographic heterogeneity. Issue 4 (21st February 2018) - Hobbelink, Sanne M. R.; Brockley, Cain R.; Kennedy, Rachel A.; Carroll, Kate; de Valle, Katy; Rao, Padma; Davis, Mark R.; Laing, Nigel G.; Voermans, Nicol C.; Ryan, Monique M.; Yiu, Eppie M.
Abstract: Introduction: The nerve sonographic features of Dejerine‐Sottas disease (DSD) have not previously been described. Methods: This exploratory cross‐sectional, matched, case–control study investigated differences in nerve cross‐sectional area (CSA) in children with DSD compared to healthy controls and children with Charcot–Marie–Tooth disease type 1A (CMT1A). CSA of the median, ulnar, tibial, and sural nerves was measured by peripheral nerve ultrasound. The mean difference in CSA between children with DSD, controls, and CMT1A was determined individually and within each group. Results: Five children with DSD and five age‐ and sex‐matched controls were enrolled. Data from five age‐matched children with CMT1A was also included. Group comparison showed no mean difference in nerve CSA between children with DSD and controls. Individual analysis of each DSD patient with their matched control indicated an increase in nerve CSA in three of the five children. The largest increase was observed in a child with a heterozygous PMP22 point mutation (nerve CSA fivefold larger than a control and twofold larger than a child with CMT1A). Nerve CSA was moderately increased in two children—one with a heterozygous mutation in MPZ and the other of unknown genetic etiology. Conclusions: Changes in nerve CSA on ultrasonography in children with DSD differ according to the underlying genetic etiology, confirming the variation in underlying pathobiologic processes and downstream morphological abnormalities of DSD subtypes. Nerve ultrasound may assist in the clinical phenotyping of DSD and act as an adjunct to known distinctive clinical and neurophysiologic findings of DSD subtypes. Larger studies in DSD cohorts are required to confirm these findings. Abstract : This cross‐sectional study evaluated peripheral nerve cross‐sectional area, as measured by nerve ultrasound, in five children with Dejerine–Sottas disease (DSD) compared to matched healthy controls and children with Charcot–Marie–Tooth disease type 1A (CMT1A). This study demonstrated marked heterogeneity in nerve enlargement in DSD, reflecting differences in genetic etiology and underlying pathobiology.